Material Conditions of Man’s Creative Activity - Morkūnas, Zigmantas (Problemos, 1973)
The article deals with some methodological problems relevant to material conditions for human creative work. These conditions become an object of scientific study only then if they emerge historically or if they are in the making. In the history or human thought these conditions were first discovered by the classics or Marxism-Leninism. The human creative work is possible only when man is free from physical need. The presence of such freedom is dependent on the factors organically correlated, such as the degree of man's domination over nature (i.e., level of productive forces) and the degree of domination over the self (i.e., level of material exchange between society and nature). The historical dependence and interrelation or the features of that domination, coinciding with humanization and creative remaking of the world, are revealed.